Perspectives and perceptions on the consumption of a healthy diet in Soweto, an urban African community in South Africa - Pretorius, Sandra; Sliwa, Karen (SA Heart Journal, 2017)
In Soweto, like in many other urban communities in sub-Saharan Africa, rapid urbanisation and epidemiological transition have left this urban African population vulnerable to diseases of lifestyle such as obesity, cardiovascular disease, hypertension and diabetes. The Heart of Soweto (HOS) study was established to examine the emergence of heart disease in Soweto and other African communities in epidemiological transition and found multiple threats to the current and future heart health of Soweto. Food intake data from the HOS has shown damaging food choices and potential nutritional deficiencies in a subgroup of urban black African patients diagnosed with CHF, living in Soweto. This preliminary data focused on the impact of changing dietary patterns, low income levels and a probable lack of knowledge of what constitutes a healthy diet and the contribution of these, to cardiovascular disease. It seems that the traditional diet is being abandoned in favour of a more Western diet typified by increased consumption of processed and convenience foods, and therefore an increased intake of salt, sugar and saturated fat. The decreased intake of fruit and vegetables has lead to a decreased consumption of fibre and vitamins and minerals. The traditional diet is associated with a low prevalence of degenerative diseases, whereas the Western diet is associated with increased prevalence. Factors that might possibly contribute to the change in dietary patterns include socio-economic circumstances, urbanisation, food insecurity, awareness around healthy food choices, as well as perceptions on obesity and overweight. Our comparison, based on currently available food prices, shows that the consumption of a healthy diet in Soweto represents a more cost effective and affordable choice than an unhealthy diet. Healthy food choices therefore, should be promoted both from a health, as well as a financial perspective. Creating awareness around risk factors that might contribute to chronic diseases of lifestyle and the prevention thereof, has become essential in this urban African population. Nutrition education and intervention programmes should focus on foods that are varied, available, culturally acceptable and popular, with the emphasis on affordability, as well as being consistent with the South African Food Based Dietary Guidelines.